2021
DOI: 10.1038/s41388-021-01847-w
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase 2 promotes tumorigenicity of colon cancer cells by inactivation of the tumor suppressor p53

Abstract: Despite a high clinical need for the treatment of colorectal carcinoma (CRC) as the second leading cause of cancer-related deaths, targeted therapies are still limited. The multifunctional enzyme Transglutaminase 2 (TGM2), which harbors transamidation and GTPase activity, has been implicated in the development and progression of different types of human cancers. However, the mechanism and role of TGM2 in colorectal cancer are poorly understood. Here, we present TGM2 as a promising drug target.In primary patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 60 publications
2
22
0
1
Order By: Relevance
“…The expression of these genes is increased in human colon cancer tissues in comparison to normal tissues, and is associated with tumorigenesis. 37,38 The increased expression of these genes was further confirmed by RT-qPCR analysis. As shown in Fig.…”
Section: Molecular Biological Characteristics Of Hectorite-induced Sp...mentioning
confidence: 70%
“…The expression of these genes is increased in human colon cancer tissues in comparison to normal tissues, and is associated with tumorigenesis. 37,38 The increased expression of these genes was further confirmed by RT-qPCR analysis. As shown in Fig.…”
Section: Molecular Biological Characteristics Of Hectorite-induced Sp...mentioning
confidence: 70%
“…After careful literature research, we found that SELENBP1 that owned lower expression in the low AIDPS group with poor prognosis was associated with better tumor prognosis, and its decreased expression led to poor prognosis of many tumors such as lung adenocarcinoma ( Chen et al, 2004 ). Meanwhile, PRR11 , EREG , ADM, and TGM2 , which were overexpressed in the low AIDPS group, played a vital role in the proliferation, invasion, and metastasis of many tumors such as breast cancer, colorectal cancer, and PACA, and lead to their chemotherapy resistance and were potential targets for enhanced efficacy ( Lee et al, 2020 ; Neufert et al, 2013 ; Aggarwal et al, 2012 ; Malkomes et al, 2021 ). In addition, our study also found strong biological correlations among nine AIDPS genes, which are also closely related to mutations, CNAs, and TME in PACA.…”
Section: Discussionmentioning
confidence: 99%
“… In addition, currently one of the few studies supports the oncogenic role of cell division cycle-associated protein 4 (CDCA4) in tumors and nuclear factors induced as E2F transcription factor families that regulate E2F-dependent transcriptional activation and cell proliferation, but their potential mechanism, especially effects on PACA tumorigenesis and progression, requires further investigation ( Fang et al, 2022 ; Hayashi et al, 2006 ). Transglutaminase 2 (TGM2), a promoter of stemness and radiotherapy resistance in glioma ( Berg et al, 2021 ), has been confirmed in many studies to promote colorectal cancer progression via P53 and Wnt/β-catenin signaling pathways ( Malkomes et al, 2021 ; Gu et al, 2019 ), as well as is associated with tumor-promoting inflammation in gastric cancer ( Cho et al, 2020 ). These results are consistent with the TGM2 expression dramatically increased in the low AIDPS group with worse prognosis, suggesting that TGM2 may play an important role in the development and progression of PACA.…”
Section: Current Research Progress On the Nine Aidps Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a general consensus that TG2 expression is upregulated in various tumors and this is associated with p53 instability [ 23 , 27 , 42 , 79 ]. In renal cell carcinoma it has been shown that the downregulation of TG2 stabilizes p53 expression, thereby inducing an increase in apoptosis.…”
Section: Direct and Indirect Tg2-dependent Regulation Of Transcriptio...mentioning
confidence: 99%